Role of mobility in cognitive development of children with motor deficyt – own observations of wheelchairs users - Mikołajewska, Emilia; Augustyńska, Beata; Mikołajewski, Dariusz (Medical and Biological Sciences, 2017)
Wheelchair plays two important roles from the physical point of view: increased mobility and body support. Two main areas of children’ development: motor and cognitive are interrelated. Thus, wheelchair supported mobility in children may also prevent many severe problems in the area of social and cognitive development. This paper aims at presentation of current state of the art and own concept concerning the role of the wheelchair-based mobility in cognitive development of children with motor deficit.